2015
DOI: 10.1308/003588415x14181254790527
|View full text |Cite
|
Sign up to set email alerts
|

Segmental colonic length and mobility

Abstract: INTRODUCTION Locoregional variation in the human colon is important in surgical practice; the length and mobility of different colonic regions impacts on laparoscopic and endoscopic colorectal procedures. The aim of this study was to refine anatomical understanding of the colon in terms of segmental length and mobility. METHODS The colons of 35 cadavers were examined to determine lengths of caecum as well as ascending, transverse, descending and rectosigmoid colon, and to characterise colonic mobility at each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…As expected, gender and age seemed to have an effect on the colonic mucus thickness. Previous studies have suggested differences in the length of the rectosigmoid colon in humans, where women were observed to have a longer rectosigmoid colon, and thus a larger mucosal surface, which may support the results [56,57]. Age was also previously reported as a factor contributing to thinner mucus in mice [58].…”
Section: Discussionsupporting
confidence: 75%
“…As expected, gender and age seemed to have an effect on the colonic mucus thickness. Previous studies have suggested differences in the length of the rectosigmoid colon in humans, where women were observed to have a longer rectosigmoid colon, and thus a larger mucosal surface, which may support the results [56,57]. Age was also previously reported as a factor contributing to thinner mucus in mice [58].…”
Section: Discussionsupporting
confidence: 75%
“…Phillips et al[ 8 ] reported colon length from several studies of cadavers, using laparotomy, barium enema or CT-colonography, between 1955 and 2015. The mean length of the colon varied between 109.0 cm and 169.0 cm.…”
Section: Newer Observations Of Colon Lengthmentioning
confidence: 99%
“…Towards the end of the first trimester, the peritoneum of the newly forming ascending colon and the hind-gut derived left colonic segments, begin to fuse with the posterior abdominal wall. Although traditionally described as retroperitoneal structures, modern post-mortem studies have found that two thirds of the ascending and a third of the descending colonic segments have mobile portions of elongated mesentery[ 7 ]. Nonetheless, peritoneal attachments have significance for the flow of free fluid within the abdomen as fluid tends to flow caudally, medial to the ascending colon towards the ileocaecal junction and thus metastatic deposits may become lodged in the mesenteric ruffles en route.…”
Section: Review Of Intestinal Embryologymentioning
confidence: 99%
“…Relative thickenings of the mesocolon provide ligamental support to the colonic flexures; the nephrocolic ligament runs from the inferior aspect of the right kidney to the hepatic flexure which then becomes intimately related to the descending duodenum before the transverse mesocolon begins; the splenic flexure is suspended by (1) the phrenicocolic ligament which runs from the diaphragm and also supports the spleen; (2) the splenocolic; and (3) the pancreaticocolic ligaments which are essentially extensions of the transverse mesocolon[ 5 , 7 ]. These attachments provide fixed points for ultrasound evaluation of the colon, which can at times, be highly mobile within the abdomen.…”
Section: Review Of Intestinal Embryologymentioning
confidence: 99%